Computational thinking ability in mathematics learning of exponents in grade IX - Salwadila, Tiara; Hapizah, Hapizah (IKIP Siliwangi and I-MES, 2024)
In the PISA 2021 framework, Computational Thinking (CT) is described as a detailed mathematical solution to the problem to be solved. However, CT-based learning still needs to be widely applied in Indonesia. This study aims to describe the CT ability of students in grade IX of junior high school based on CT indicators on the material of signed numbers. The data collection techniques in this study were test questions and interviews. Students who obtained high categories with scores above 45.76 were six students with a percentage of 21%, students who received medium categories with scores between 11.94 and 45.76 were 19 students with a rate of 66%, and students who obtained low categories with scores below 11.94 were four people with a percentage of 13%. The results of the study state that as many as 39% of students can decompose the problems given, 17% of students can recognize patterns in the problem, 24% of students can sort out the information in the situation or abstract, and 26% of students can solve problems well according to algorithm indicators.